Enhancing Construction Waste Transportation Management Using Internet of Things (IoT): An Evaluation Framework Based on AHP–FCE Method - Muhammad Ateeq; Nan Zhang; Wenbo Zhao; Yaoqian Gu; Ziying Wen; Caimiao Zheng; Jianli Hao (Buildings)
The transportation of construction waste involves various complexities, including logistics, monitoring, and resource management. Nevertheless, conventional transportation methods struggle to meet the combined requirements of environmental sustainability and efficiency in modern urban development due to problems such as high idle rates and insufficient management. The swift advancement of Internet of Things (IoT) technology offers an innovative solution for the intelligent and effective management of construction waste transportation in response to these issues. This study explores how IoT technology can enhance construction waste transportation management by developing an evaluation framework using the Delphi method, analytic hierarchy process (AHP), and fuzzy comprehensive evaluation (FCE). This research focuses on the application of IoT to optimize the transportation and logistics process through real-time monitoring and data analysis. The capability of IoT technology to analyze real-time data facilitates the modification of routes to minimize empty mileage and transportation time, thus improving transport efficiency. Ultimately, the potential and challenges of IoT in construction waste transportation management have been discussed.